Clinical outcomes and risk factors of non-curative endoscopic submucosal dissection for early gastric cancer: a retrospective multicenter study in Zhejiang, China - Jin, Chao-qiong; Zhao, Jing; Ding, Xiao-yun; Yu, Liang-liang; Ye, Guo-liang; Zhu, Xin-jian; Shen, Jian-wei; Yang, Ye; Jin, Bo; Zhang, Chun-li; Lv, Bin (Frontiers in Oncology, 2023)
Background Endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) does not always lead to curative resection. Risk factors of lymph node metastasis (LNM)/local cancer residue after non-curative ESD for EGC have not been fully elucidated. We therefore aimed to clarify them and evaluate whether the “eCura system” is reliable for the risk stratification of LNM after non-curative ESD. Methods We conducted a multicenter retrospective study at seven institutions in Zhejiang, China, on 128 patients who underwent non-curative ESD for EGC. We divided the patients into two groups according to their therapeutic regimen after non-curative ESD. We analyzed the risk factors for LNM, local cancer residue, cancer recurrence, and cancer-specific mortality. Furthermore, we compared the outcomes in each risk category after applying the “eCura system”. Results Among 68 patients undergoing additional surgery, LNM was found in three (4.41%) patients, while local cancer residue was found in eight (11.76%) patients. Multivariate analysis showed that upper third location and deep submucosal invasion were independent risk factors of LNM and local cancer residue. Among 60 patients who underwent simple follow-up, local cancer recurrence was found in four (6.67%) patients and cancer-specific mortality was found in one (1.67%) patient. There were no independent risk factors of cancer recurrence and cancer-specific mortality in our study. During the follow-up period, 5-year overall survival (OS) and disease-free survival (DFS) were 93.8% and 88.9%, respectively. Additionally, LNM and cancer recurrence were significantly associated with the eCura scoring system (p = 0.044 and p = 0.017, respectively), while local cancer residue and cancer-specific mortality were not (p = 0.478 and p = 0.131, respectively). Conclusion Clinicians should be aware of the risk factors for the prognosis of patients with non-curative ESD to determine subsequent treatment. Through the application of the “eCura system”, additional surgery should be performed in patients with intermediate/high risk of LNM.